Analisis Kekuatan Pembebanan Frame Pada Meja Las - Yusuf Dewantoro Herlambang; Wahyu Triharto Prabowo; Fatahul Arifin; Ramadoni; Willy Ravindo H Damanik (Jurnal INOVATOR, 2023)
Welding machine is a machine that facilitates human work in joining metals. There are two types that are usually used by humans, namely carbide welding machines and electric welding machines. Which both have their respective advantages as a metal connector. This article is lifted from the problem that occurs in the frame or frame on the welding table which experiences severe enough bending of the top frame (head support) which can damage the table frame and the unknown load (force) received by the welding table frame so that the frame is experiencing a bend. Then a design is carried out in the form of a design drawing that can be analyzed for the strength and stress that occurs in the frame which allows researchers to know the load value that is safe to use for the frame. This article aims to reveal the value of the stress that occurs in the frame and the safety value obtained from the design results of the weld table frame structure in the form of technical drawings and structural strength analysis. This article is limited to a loading of 400 newtons. This article examines the design, simulation and stress analysis of the weld table frame structure with a capacity of 400 newtons using the finite element method or also known as Finite Element Analysis (FEA). The material used is st37 iron. Finite element analysis was carried out using a numerical system using the Autodesk Inventor Professional 2020 software. The results of the simulations and also the analysis that has been carried out show that the welding table frame structure has a stress, deformation, mass, and safety factor of 20.0755 MPa, 0.0582948 mm, 40 kg